Articulation of technologies through the career Professor of Mathematics at the National University of Rosario - Bonservizi, Virginia Magali (2021)
This paper analyzes the modes of articulation of technologies in the different curricular activities of a teacher training career in Mathematics in Argentina. The components of disciplinary-pedagogical-technological knowledge are considered as a frame of reference. An open online questionnaire is applied to the professors of the career as the first phase of inquiry, through a qualitative approach and case study design. Among the categories of interest, there are activities with technologies as well as their supports and foundations given by teachers, those experiences that are especially valued with the relevance they give for the training of trainers and, finally, some emerging comparisons from the technological irruption due to the pandemic situation. In general terms, it has been possible to verify that the experiences reported are very varied among themselves, some with a potential to be developed and others with substantial practices that are distinctive.